Green Extraction of Bioactive Compounds from Apple Pomace from the Cider Industry - Rosa Pando Bedriñana; Roberto Rodríguez Madrera; María Dolores Loureiro Rodríguez; Karelmar López-Benítez; Anna Picinelli Lobo (MDPI AG, 2024)
The cider-making industry in Asturias generates between 9000 and 12,000 tons of apple pomace per year. This by-product, the remains of the apple pressing, and made up of peel, flesh, seeds and stems, is a valuable material, containing substantial amounts of antioxidant compounds associated with healthy properties. Polyphenols such as dihydrochalcones and quercetin glycosides, and triterpenic acids, among which ursolic acid is a major compound, are the main antioxidant families described in apple pomace. The simultaneous recovery of those families has been accomplished by low frequency ultrasound-assisted extraction. Working extraction conditions were optimised by response surface methodology (RSM): time, 5.1 min; extractant composition, 68% ethanol in water; solid/liquid ratio, 1/75 and ultrasonic wave amplitude, 90%. This procedure was further applied to analyse those components in the whole apple pomace (WAP), apple peel (AP) and apple flesh (AF). On average, dry WAP contained almost 1300 µg/g of flavonols, 1200 µg/g of dihydrochalcones and 4200 µg/g of ursolic acid. These figures increased in the apple peel to, respectively 2500, 1400 and 8500 µg/g dry matter. Two linear multivariate regression models allowed the antioxidant activity of apple by-products to be predicted on the basis of their bioactive composition. The results derived from this study confirm the potential of industrial cider apple pomace as a source of high-value bioactive compounds, and the feasibility of the ultrasound-assisted extraction technique to recover those components in a simple and efficient way.